Montmorilonita sódica na dieta de frangos de corte intoxicados com aflatoxina - Dullius, Ana Paula (2013)
The objective of this dissertation was to evaluate the impacts of aflatoxin in a concentration of 2,8mg/kg, and sodic montmorillonite on performance, enzyme activity and liver function in broilers from 1 to 21 days, as well as compare to other products already on the market. Were utilize 540 chickens housed in cages. Experimental design was completely randomized, with 9 treatments and 6 replications. The treatments were: Control (basal diet), Ads0,50 (basal diet + 0,50% Test adsorbent), Afla (basal diet + 2,8mg/kg of Aflatoxin), Ads0,25 + Afla (basal diet + 0,25% Test adsorbent + 2,8mg/kg of Aflatoxin), Ads0,50 + Afla (basal diet + 0,50% Test adsorbent + 2,8mg/kg of Aflatoxin), AdsA + Afla (basal diet + 0,50% A adsorbent + 2,8mg/kg of Aflatoxin), AdsB + Afla(basal diet + 0,50% B adsorbent + 2,8mg/kg of Aflatoxin), AdsC + Afla (basal diet + 0,50% C adsorbent + 2,8mg/kg of Aflatoxin), AdsD + Afla (basal diet + 0,50% D adsorbent + 2,8mg/kg of Aflatoxin). The adsorbents A, B, C, D are based sodic montmorillonite, but come from different companies. The data collected were subjected to analysis of variance and comparison of means by Tukey test (P ≤ 0.05). It is concluded that the test adsorbent in a concentration of 0,50% was effectively promoted and a reduction of toxic effects of aflatoxin on performance of broilers at 21 days of age but did not avoided changes in liver function and liver enzymes. And gave results similar to the products C and D, and higher than product B.